Partisipasi Masyarakat dalam Mengikuti Kelas Parenting Puspaga - Rizky ; Buana Sari; Bayu Priambodo (SOCIETAS, 2024)
The low level of community participation in Manukan Kulon Subdistrict in the PUSPAGA parenting class program reflects the gap between the aim of supporting children's development and the reality on the ground. This condition is caused by daily demands such as work and household matters. This research aims to describe the forms and factors of community participation in attending PUSPAGA parenting classes in Manukan Kulon Village, Surabaya City. This research uses descriptive qualitative research methods and collects data through observation and interviews. The data in this research was analyzed using an interactive approach which includes data collection, data simplification, data presentation, and drawing verification/conclusions. The results of the research show that the community in Manukan Kulon Subdistrict has participated in taking parenting classes by involving the participation of ideas through meetings of local officials regarding decision making for the PUSPAGA program, energy participation by contributing in preparing facilities and infrastructure, and social participation by motivating the community to take parenting classes. , and participation in property through borrowing infrastructure and donating food. Internal factors, such as gender, namely the majority of mothers have flexible time, age, namely adults and the elderly tend to participate more, high level of education influences participation. Meanwhile, busy work is an obstacle to participation. External factors, such as leadership and communication, namely local tools, motivate people to take parenting classes both in person and online.